Do the Techniques Really Improve Students’ Mastery in Vocabulary? - Susiati Susiati; Nina Kartikasari (Journal of English Education and Teaching, 2020)
This study describes the techniques applied by teachers in teaching English vocabulary to the tenth grade students at Muhammadiyah Boarding School 1 Weleri. This study aims to determine and describe the techniques used by teachers on how teachers apply these techniques in teaching English vocabulary, and analyze the responses of students regarding the techniques used by teachers in vocabulary learning. The subjects of this study were two teachers and six tenth grade students at Muhammadiyah Boarding School 1 Weleri. The method used is descriptive qualitative. The research was obtained by observation, interview and documentation. The results of this study, researchers found five techniques used by both teachers in teaching English vocabulary. Teacher A techniques used are: (a) example sentences, (b) word syntaxes, (c) translating with dictionaries, (d) practice (oral drills and practice exercises), and (e) memorization. Teacher B techniques used are: (a) equality of words / opposites, (b) translating, (c) practice, and (e) memorization. Students‘ responses in general can accept the techniques used by both teachers, which can be seen from the attitudes, activeness, and enthusiasm of students when attending lessons. Students have different responses to the techniques used by teacher A and teacher B. With the techniques applied by the teacher in vocabulary learning, students‘ get improvement in learning English.